Types of Flouting Maxim in Me Before You Movie - Ni Kadek Lili Anto Nela; I Gusti Ayu Vina Widiadnya Putri (Universitas Cokroaminoto Palopo, 2024)
The objective of this study is to identify the specific instances in which the maxims of conversation are deliberately violated in the movie “Me Before You”. The movie serves as the primary data source for this investigation. The data in this study was gathered through the utilization of a content analysis methodology and a note-taking approach. The data is studied utilizing qualitative methodologies and interactive model analysis, encompassing data collection, reduction, exploration, drawing conclusions, and verification. Two theories used to analyze research findings. The leading theory is from Grice's (1975) Logic and Conversation, and the second theory is The Shameless Liar's Guide by Christofferson (2005). The research findings show there are sixteen flouting maxims in the film Me Before You. The flouting maxim of quantity becomes the flouting maxim with the highest frequency, ten times (62,5%). However, each of the violations committed by the characters in Me Before You does not interfere with the overall flow of communication.